Friction characteristics of RBD palm olein using four-ball tribotester - Syahrullail, S. (2013)
In this study, the effect of load on the tribological performance of RBD palm olein is investigated using a four-ball wear tester according to the standard test of ASTM D4172. Tests were conducted with 40, 60, 80, 100 and 120 kg normal loads. The experimental temperature and rotational speed were held constant at 75°C and 1200 rpm, respectively. The test duration was 60 minutes in all cases. For each load, the tribological properties of RBD palm olein were compared with the properties of additive-free paraffinic mineral oil. The results focused on the frictional torque, wear scar diameter, friction coefficient and the flash temperature. Following the completion of the wear test experiments, the ball wear condition and lubricant properties were observed. These results show that RBD palm olein has a lower coefficient of friction than paraffinic mineral oil; however showed a high oxidation effect under high temperature work conditions.